2020
DOI: 10.1108/jarhe-05-2020-0141
|View full text |Cite
|
Sign up to set email alerts
|

The mediating role of self-congruity in transnational higher education choice: a proposed framework

Abstract: PurposeThis paper aims to propose a conceptual framework to bridge the gap between the dimensions of brand equity (brand awareness, brand association and perceived quality) and the purchase intention of transnational higher education.Design/methodology/approachThe paper revisits and critically reviews the concepts of marketing in higher education, brand equity, and self-congruity as well as related past studies.FindingsSeveral past empirical studies concluded that the dimensions of brand equity have been unabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 79 publications
(112 reference statements)
3
3
0
Order By: Relevance
“…The unsupported H1, that brand awareness does not relate positively to enrollment intention, further justifies the research gap of this study. It aligns with the results of many recent empirical studies that contrast the Theory of Brand Equity across different goods and services and consumer settings (Sudhana, Noermijati, Sabil Hussein, & Khusniyah Indrawati 2021). The unsuccessful relationship warrants fundamental research to explain the underlying mechanism of the failed relationship between external cues and behavioral intention.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The unsupported H1, that brand awareness does not relate positively to enrollment intention, further justifies the research gap of this study. It aligns with the results of many recent empirical studies that contrast the Theory of Brand Equity across different goods and services and consumer settings (Sudhana, Noermijati, Sabil Hussein, & Khusniyah Indrawati 2021). The unsuccessful relationship warrants fundamental research to explain the underlying mechanism of the failed relationship between external cues and behavioral intention.…”
Section: Discussionsupporting
confidence: 81%
“…The positive and direct association between brand equity and purchase intention has been well documented (Bian & Liu, 2011;Wang & Li, 2012). Brand equity can be operationalized as multidimensional, consisting of brand awareness, brand loyalty, perceived quality, brand associations, other proprietary assets (Sudhana, Noermijati, Sabil Hussein, & Khusniyah Indrawati, 2021). Brand awareness is defined as the strength of a brand's presence in the target audience's minds over time (Rodríguez-López, del Barrio-García, & Alcántara-Pilar, 2020).…”
Section: Developing Hypothesesmentioning
confidence: 99%
“…The unsupported H1 aligns with some evidence which suggest that brand awareness may not always directly affect purchase intention (Sudhana et al. , 2021).…”
Section: Discussionsupporting
confidence: 79%
“…The unsupported H1 aligns with some evidence which suggest that brand awareness may not always directly affect purchase intention (Sudhana et al, 2021). For example, consumers may be aware of a brand but still choose to purchase a competitor's product because it better meets their needs or preferences (Oke et al, 2016).…”
Section: Discussionsupporting
confidence: 57%
“…The highlighted theoretical gap in this study is that the awareness of the esteemed international education brands has been unable to influence the enrolment intention, in contrast to the theory of brand equity. Many recent empirical studies revealed similar results and inconsistencies across different goods and services, consumer populations and consumption settings (Sudhana et al, 2021). This study aims to understand the underlying mechanism explaining the unsuccessful relationship between the two variables.…”
Section: Introductionmentioning
confidence: 88%